El recurso pesquero de guapote (Cichlasoma dovii) en el Embalse de Arenal, Costa Rica - Campos, Jorge A. (Revista de Biología Tropical, 1986)
A ten day study of the Guapote Cichlasoma dovii (Gunther, 1964) was carried out in Lake Arenal Fishes were captured using gillnets, hooks and lines, and longlines. This information plus other obtained from records of fishing con tests were used as imput for several algorithms that use size frecuency data. The explotation rate (E) of the guapote is 0.59. The value of y max was 0.41 Y. These two results indicate that the resource is overexploited. Information regarding the distribution of the species, several aspects of its biology and recomendations for the management of the resource are also offered.